PETROLOGY AND TECTONIC SIGNIFICANCE OF GREENSCHISTS FROM THE MEDVEDNICA MTS. (SAVA UNIT, NW CROATIA) - Lugović, Boško; Šegvić, Branimir; Altherr, Rainer (Ofioliti, 2006)
The Lower Cretaceous (123-115 Ma) low-grade metamorphic complex of the Medvednica Mts. is located within the southwestern edge of the Mid-Trans- Danubian shear zone. The SW-NE striking complex consists of metabasites overlain by metasediments, both affected by a single metamorphic event. Metamorphic parageneses and mineral compositions of the metabasites indicate greenschist facies conditions in the SE part and upper greenschist facies conditions in the NW one. Temperature estimates based on chlorite thermometry are consistent with temperatures derived from petrogenetic grids. Chemical compositions of the metabasites are likely controlled by pre- and syn-metamorphic modifications. Nevertheless, “immobile” element characteristics (HFSE, REE) indicate a subalkaline nature of the igneous precursors. Most probably, the protoliths were subduction-related low-K tholeiitic basalts. Structural analysis suggests that the greenschists of the Medvednica Mts. were formed during southwest-vergent obduction of Jurassic to Lower Cretaceous ophiolites onto the Dinaridic continental margin composed of Ordovician to Upper Triassic sedimentary and volcano-sedimentary successions. The petrological and geochemical investigations thus indicate that an island arc was involved in the obduction that formed the Medvednica Mts. low-grade metamorphic complex.